Silicon and potassium synergistically alleviate salt stress and enhance soil fertility, nutrition, and physiology of passion fruit seedlings - Silva, Alicia Camila Zeferino da; Pereira, Rennan Fernandes; Ferreira, Raquel da Silva; Alves, Samuel Barbosa; Sousa, Franklin Suassuna de; Rodrigues, Samuel Saldanha; Brito Neto, José Felix de; Melo, Alberto Soares de; Silva, Roseano Medeiros da; Mesquita, Evandro Franklin de (Frontiers in Plant Science, 2025)
IntroductionYellow passion fruit (Passiflora edulis) is widely cultivated in Brazil but suffers adverse effects when irrigated with saline water, a common condition in the Brazilian semiarid region. Silicon and potassium have been extensively studied as salt stress mitigators, yet little is known about the synergistic effects between these two elements. Therefore, we evaluated the synergistic effects of silicon and potassium on alleviating salt stress in yellow passion fruit seedlings.MethodsThe experiment was conducted in a greenhouse using a completely randomized 4 × 2 + 2 factorial design with five replicates. Four doses of silicic acid (1.26, 2.52, 3.78, and 5.04 g dm-3) and two potassium doses (150 and 600 mg dm-3) were tested, with two controls (saline and non-saline water). Soil fertility (pH, electrical conductivity, mineral elements) and the following plant variables were assessed: foliar concentrations of macro- and micronutrients, biochemical traits (chlorophyll and proline), gas exchange, relative water content, electrolyte leakage, growth, and biomass accumulation. ANOVA (F-test) was performed, with regression and Dunnett’s test used for significant effects.ResultsThe silicon-potassium combination reduced soil pH and electrical conductivity, while increasing the availability of P, K, Ca, Mg, S, Fe, Mn, Zn, and Cu. Foliar nutrient concentrations improved while leaf Na+ decreased. Biochemically, there was a significant increase in total chlorophyll, along with reduced proline levels. Plants also exhibited higher CO2 assimilation, stomatal conductance, and relative water content, with reduced electrolyte leakage. Plant height and shoot and root dry masses increased in response to silicon doses, with gains of up to 133% compared to the saline control.DiscussionSilicon and potassium acted synergistically to reduce soil and leaf salinity, improve nutrient availability, and enhance plant biochemical and physiological performance, leading to greater growth and biomass accumulation. The results support the combined application of silicon and potassium as an effective strategy to mitigate salt stress and promote the nutrition, physiology, and growth of yellow passion fruit seedlings under saline irrigation.